Paradoxical impact of asymmetric regulation in Taiwan’s mobile communications - CHOU, Yuntsai (Institutional Knowledge at Singapore Management University, 2007)
The mobile penetration rate in Taiwan has climbed from 6.86 to 112.15 mobile phone accounts per 100 capita in the first six years of market competition, during which the state-owned incumbent Chunghua Telecom was dethroned by a new entrant, Taiwan Cellular Corp. This paper addresses the cause of Taiwan’s unprecedented mobile growth, and provides policy solutions for countries that strive to improve their telecommunications sectors in a short time. The authors highlight the fundamental role of asymmetric regulation, rather than pure liberalization, in the creation of the deregulated telecommunications industry in Taiwan. The asymmetric regulation in Taiwan is manifested in a twofold framework: the dominant carrier versus competitors, and the fixed-line carrier versus mobile companies. An econometric analysis concludes that dualistic asymmetric regulation leads to higher growth for mobile competitors and raises the total mobile penetration rate. However, the authors warn against the paradoxical consequences of dualistic asymmetric regulation. The regulatory benefits which mobile entrants received evolved into rents when they successfully lobbied to end the follow-me call service, the pricing scheme of which contradicts the asymmetric revenue-sharing constraint. The paper calls for a sunset clause for dualistic asymmetric regulation in order to take full advantage of its strengths, while at the same time preventing rent-seeking by the firms which benefit.